1985
DOI: 10.1073/pnas.82.14.4828
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine produced in rat synaptosomes by N-methylation is enriched in polyunsaturated fatty acids.

Abstract: Rat brain synaptosomes contain an enzyme, phosphatidylethanolamine N-methyltransferase (EC 2.1.1.17), that catalyzes the methylation of phosphatidylethanolamine to form its mono-, di-, and trimethyl (phosphatidylcholine) derivatives. Synaptosomal phosphatidylethanolamine is much richer in polyunsaturated fatty acids (43.4%) than is synaptosomal phosphatidylcholine (4.6%). It thus seemed possible that the phosphatidylcholine derived via the Nmethylation of phosphatidylethanolamine might also be especially enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
2
25
1
2
Order By: Relevance
“…Bovine ROS do not support the de novo synthesis of phosphatidylcholine (PC), but they contain an alternative pathway catalyzed by PE N-MTase (Roque and Giusto, 1995). The PE N-MTase activity in ROS could be responsible for the synthesis of PC molecules enriched in polyunsaturated fatty acids, a phenomenon which is in agreement with previous observations in the brain and liver (Ridgway and Vance, 1988 ;Tacconi and Wurtman, 1985). It has recently been demonstrated that PE N-MTase in isolated ROS is modulated by light and by a mechanism involving specific protein kinases and phosphatases in vitro .…”
Section: Introductionsupporting
confidence: 71%
“…Bovine ROS do not support the de novo synthesis of phosphatidylcholine (PC), but they contain an alternative pathway catalyzed by PE N-MTase (Roque and Giusto, 1995). The PE N-MTase activity in ROS could be responsible for the synthesis of PC molecules enriched in polyunsaturated fatty acids, a phenomenon which is in agreement with previous observations in the brain and liver (Ridgway and Vance, 1988 ;Tacconi and Wurtman, 1985). It has recently been demonstrated that PE N-MTase in isolated ROS is modulated by light and by a mechanism involving specific protein kinases and phosphatases in vitro .…”
Section: Introductionsupporting
confidence: 71%
“…In our studies of rat brain, we were unable to detect any 13 C labeling on PtdC in either whole brain experiments (12) or in the current investigation involving specific brain areas. Furthermore, the literature suggests that the activity of PEMT is extremely low in adult brain tissue thus making any contributions from the pathway negligible (28)(29)(30). We have also conducted NMR studies in neonate rat brains following administration of 13 C-labeled ethanolamine, which also failed to show any appreciable synthesis of PtdC via the PEMT pathway (unpublished data).…”
Section: Phospholipid Profilementioning
confidence: 88%
“…In those reports the identity of the phospholipases mediating arachidonic acid release was not assessed directly. The Phosphatidylcholine arising from the receptor-mediated methylation of phosphatidylethanolamine is rich in arachidonic acid (28,29). In unstimulated FRTL5 cells, arachidonic acid is preferentially incorporated into phosphatidylethanolamine (R.M.B., unpublished data).…”
Section: Discussionmentioning
confidence: 99%